Combinatorial microneedle patch with tunable release kinetics and dual fast-deep/sustained release capabilities. Issue 9 (2nd March 2021) - Lopez-Ramirez, Miguel Angel; Kupor, Daniel; Marchiori, Leonardo; Soto, Fernando; Rueda, Ricardo; Reynoso, Maria; Narra, Lakshmi Rekha; Chakravarthy, Krishnan; Wang, Joseph
Abstract : This manuscript introduces a combinatorial microneedle patch with variable dissolution rate and tunable release in a single application; it delivers payloads in minutes while simultaneously deliver dosages from weeks to months with constant release. Abstract : Transdermal microneedle (MN) drug delivery patches, comprising water-soluble polymers, have played an essential role in diverse biomedical applications, but with limited development towards fast deep release or sustained delivery applications. The effectiveness of such MN delivery patches strongly depends on the materials from which they are constructed. Herein, we present a dual-action combinatorial programmable MN patch, comprising of fast and sustained-release MN zones, with tunable release kinetics towards delivering a wide range of therapeutics over different timeframes in single application. We demonstrate the fine tuning of MN materials; the patches can be tailored to deliver a first payload faster and deeper within minutes, while simultaneously delivering a second payload over long times ranging from weeks to months. The active and rapid burst release relies on embedding biodegradable Mg microparticle 'engines' in dissolvable MNs while the sustained release is attributed to biocompatible polymers that allow prolonged release in a controllable tunable manner. In addition, the patches are characterized and optimized for their design, materials and mechanical properties. These studies indicate that such programmable dual-action versatile MN platform is expected to improve therapeutic efficacy and patient compliance, achieving powerful benefits by single patch application at low manufacturing cost.